PHRASEOLOGY AND INSTITUTIONAL DISCOURSE: ANGELA MERKEL - Sedykh, Arkadiy; Dugalich, Natalia; Dmitrieva, Elena; Usmanova, Zulfiya; Kupriyanova, Milana (Revista Inclusiones, 2020)
The article presents the linguosemiotic approach to the study of phraseological units used by an institutional language personality. It enlists theoretical prerequisites for modeling this type of personality. The explicit meaning of an utterance is regarded as the key element highlighting features of phraseological communication. Other levels are considered during the contrastive description of institutional text and complement the essential parameters conveyed by the structure of ethnocultural code that underlies the construction of statements in national language. The language personality of a politician, in particular Angela Merkel, is considered as an active mechanism for the functioning of institutional discourse. There are certain prospects for analyzing institutional communication with due regard to the extralinguistic factors associated with the communicative competence of a recipient of institutional messages.